How to Write an Article for Comparative Population Studies - Rees, Philip H. (Comparative population studies, 2025)
This editorial is written by Philip Rees, Professor Emeritus in Population Geography at the University of Leeds, UK, drawing on his experience as external editor for Comparative Population Studies (CPoS) in 2019 and as a writer of research papers for 6 decades. He spent a busy year of emails and reviews at his desk in Leeds as part of the CPoS editorial team, with visits to Wiesbaden for editorial meetings. This experience was good preparation for the necessity of home working in 2020 and 2021 during the Covid-19 pandemic. This article provides guidance for aspiring authors of CPoS articles in preparing and revising a submission. The advice includes sticking precisely to the CPoS guidance, writing clear and concise prose, being selective in your citations, focusing on originality and relevance, and responding in full to all issues raised by the reviewers of your paper. Then you will be able to benefit from the online publication of your paper, avoiding the article charges levied by commercial publishers, rapid turnround, meticulous sub-editing, assistance if English is not your native language and wise advice from a succession of external guest editors. * This article belongs to a series celebrating the journal's 50th anniversary.